2000
DOI: 10.1002/1097-0215(20000801)87:3<349::aid-ijc7>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

HER‐2/neu is expressed in human renal cell carcinoma at heterogeneous levels independently of tumor grading and staging and can be recognized by HLA‐A2.1‐restricted cytotoxic T lymphocytes

Abstract: The HER-2/neu oncoprotein, a 185 kDa membrane-associated tyrosine kinase with extensive homology to the epidermal growth factor receptor (EGF-R), is overexpressed in breast and ovarian carcinomas. Its overexpression is closely associated with poor prognosis in the course of disease. Here we demonstrate HER-2/neu overexpression in both established cell lines and biopsy material obtained from renal epithelial tumors. Immunohistochemical analysis of human kidney tumor lesions using 2 HER-2/neu-specific antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…Therefore, the findings of the present study were consistent with those of previous studies, which indicate that the downregulation of HER2 is commonly observed in RCC cells (Table V) (17)(18)(19). The various expression patterns of HER2 have been previously discussed and, in a comparison of the subtypes of RCC, the expression of HER2 was associated with the pRCC and chRCC tumor types, but not associated with tumor grade and stage (20). These findings are similar to the statistical results of the present study, which indicated that none of the clinical characteristics correlated with each other in the FISH analysis.…”
Section: Of Cases ---------------------------------------------------supporting
confidence: 93%
“…Therefore, the findings of the present study were consistent with those of previous studies, which indicate that the downregulation of HER2 is commonly observed in RCC cells (Table V) (17)(18)(19). The various expression patterns of HER2 have been previously discussed and, in a comparison of the subtypes of RCC, the expression of HER2 was associated with the pRCC and chRCC tumor types, but not associated with tumor grade and stage (20). These findings are similar to the statistical results of the present study, which indicated that none of the clinical characteristics correlated with each other in the FISH analysis.…”
Section: Of Cases ---------------------------------------------------supporting
confidence: 93%
“…Her-2 receptor-specific tumor toxin, in an animal model, effectively reduced pulmonary tumors of advanced RCC (Maurer-Gebhard et al 1998). Parallel associations of Her-2 expression between tumor stage and grade in RCC patients have been observed in many studies (Zhang et al 1997, Stumm et al 1996, although in the study of Seliger et al (2000) no such association was found. In the study of Hofmockel et al (1997), higher tumor grades were seen when Her-2 expression was low, and higher T-stage associated with high Her-2.…”
Section: Her-2 Biomarker Of Proto-oncogene Productsupporting
confidence: 54%
“…Since this discovery, the synthetic peptide HER2 369 -377 has been widely investigated for the ex vivo and in vivo generation of HER2-specific CTLs following stimulation in vitro (39,(41)(42)(43)(44)(45)(46) and vaccination (18,38,(47)(48)(49), respectively. Results obtained from different research groups led to the conclusion that HER2 369 -377 -specific T cells can potentially lyse HLA-A2-matched HER2-overexpressing tumor cells (39,(41)(42)(43)(44)(45)(46)48) and may be even able to eliminate tumor cells in vivo (18,29,50). However, Sette and colleagues showed for the first time that HER2 369 -377 -specific CTLs generated by in vitro stimulations using the synthetic peptide HER2 369 -377 do not necessarily recognize the endogenously processed peptide and, therefore, may fail to lyse HLA-A2 ϩ HER2-overexpressing tumor cell lines (45).…”
Section: Discussionmentioning
confidence: 99%